A novel surface-cluster approach towards transient modeling of hydro-turbine governing systems in the start-up process. (1st June 2018) - Zhang, Hao; Chen, Diyi; Guo, Pengcheng; Luo, Xingqi; George, Aggidis
Highlights: A novel surface-cluster approach towards transient modeling of hydro-turbine governing systems is presented. The transient model of the hydro-turbine governing system is established in start-up process. The dynamic characteristics are investigated utilizing numerical experiments. The effects of the guide vane opening are studied in start-up process. The opening law is improved in start-up process. Abstract: Transient process, an essential condition for the operation of the hydro-turbine governing system, is critical for the safety and stability of a hydropower station. This research focuses on the transient modeling and dynamic analysis of the hydro-turbine governing system in the start-up process. A novel approach is developed to establish the dynamic model of the hydro-turbine governing system in transient process. The flow equation and torque equation were improved to reflect the dramatic changes of system parameters during the start-up process. As a pioneering work, the effect of guide vane opening law on the dynamic characteristics of the hydro-turbine governing system in the start-up process was investigated by numerical simulations. The results of this research can promote the development of transient modeling and performance improvement of hydro-turbine governing systems in transient process.